Sustainable Financial Management Practices and Firm Value: Evidence from Environmentally Responsible Companies in Indonesia - Chandika Mahendra Widaryo; Margareth Henrika; Lusiana Desy Ariswati; Muhammad Ramadhani Kesuma; Ellen D. Oktanti Irianto (Universitas Muhammadiyah Palu, 2025)
This study examines how sustainable financial management practices (SFMP) influence firm value in environmentally responsible companies in Indonesia using a phenomenological qualitative approach. The research explores managers’ lived experiences in implementing green capital budgeting, green financing, and green investment, and how these practices shape long-term value creation. Data were gathered through in-depth semi-structured interviews with finance managers, sustainability officers, and key decision-makers, supported by document analysis and limited observations.The findings show that sustainability is embedded in financial decision-making, where investment evaluations consider environmental impact, regulatory compliance, and long-term ecological benefits. Green financing appears as both a structural challenge and a strategic facilitator. While strict ESG requirements demand extensive documentation and verification, they also provide lower capital costs and serve as external validation of sustainability commitments.The study further reveals that green investments are viewed as essential for reducing regulatory and environmental risks, enhancing corporate reputation, and attracting ESG-oriented investors. A cultural shift is evident within firms, characterized by cross-department collaboration, transparency, and a managerial mindset oriented toward sustainability in financial decisions. These changes reinforce governance structures and support institutionalization of sustainability across business functions.Overall, SFMP are perceived to enhance firm value by improving reputation, lowering long-term risks, strengthening investor confidence, and increasing organizational resilience in dynamic regulatory environments. The study concludes that sustainability-driven financial practices play a transformative role in shaping corporate strategy, governance, and market positioning.